Materials modeling of Ge-based nanostructure through metalloid/metal group 13 adsorption compared to Li in ion batteries: monitoring density of states for structural, physical and electronic properties analysis - Fatemeh Mollaamin (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2026)
Boron group-based materials, with impressive capacity utilization and self-healing ability, provide better alternatives for alkali metal ion batteries that exhibit all-round performance with the balance of energy/power density and cycling stability. Germanium carbide (GeC) has been designed and characterized as an anode electrode for lithium (Li), boron (B), aluminum (Al) and gallium (Ga)-ion batteries due to forming X2(GeC) (X = Li, B, Al, Ga) nanoclusters. A vast study on energy-saving by X2(GeC) complexes was probed using computational approaches due to density state analysis of charge density differences (CDD), total density of states (TDOS) and molecular electrostatic potential (ESP) for hybrid clusters of X2(GeC). A small portion of Li, B, Al or Ga entered the Ge–C layer could improve the structural stability of the electrode material at high multiplicity, thereby improving the capacity retention rate. Higher Ge/C content can increase battery capacity through X2(GeC) nanoclusters for energy storage process and improve the rate performances by enhancing electrical conductivity. Besides, GeC anode material may advance cycling consistency by excluding electrode decline and augments the capacity owing to higher surface capacitive impacts. In this research article, the recent progress of boron, aluminum or gallium -based anodes and their storage mechanism is presented.